THE EFFECT OF THE POE2WE LEARNING MODEL ASSISTED BY STUDENT WORKSHEETS ON STUDENTS' SCIENCE LEARNING OUTCOMES - Lastri Handayani; Monica Prima Sari; Yurnetti; Febri Yanto (Universe, 2026)
Students' learning outcomes in science remain a major concern due to the limited effectiveness of conventional instructional approaches in fostering meaningful learning. Preliminary observations at SMPN 1 Nan Sabaris indicated that students' science learning outcomes were relatively low, highlighting the need for more innovative and student-centered learning models. This study aimed to examine the effect of the POE2WE (Prediction, Observation, Explanation, Elaboration, Write, and Evaluation) learning model assisted by Student Worksheets on students' science learning outcomes. A quasi-experimental research design employing a posttest only control group design was used. The participants were selected through purposive sampling, with one class assigned as the experimental group receiving instruction using the POE2WE learning model assisted by Student Worksheets, while another class served as the control group receiving conventional instruction. Data were collected using two assessment instruments: a 25-item multiple-choice test to measure students' cognitive learning outcomes and a performance assessment rubric to evaluate psychomotor skills. The data were analyzed using an independent-samples t-test. The findings revealed that the experimental group achieved significantly higher cognitive and psychomotor learning outcomes than the control group. These results indicate that the implementation of the POE2WE learning model assisted by Student Worksheets (LKPD) has a significant positive effect on students'science learning outcomes. Therefore, the POE2WE learning model can be considered an effective instructional approach for improving students' learning outcomes in science education.